2000
DOI: 10.1021/np000038p
|View full text |Cite
|
Sign up to set email alerts
|

Two New Malyngamides from a Madagascan Lyngbya majuscula

Abstract: The lipid extract of a Madagascan Lyngbya majuscula has yielded malyngamides Q and R, both amides of 7-methoxytetradec-4-enoic acid. The isolation of these metabolites was accomplished using preparative liquid chromatography, with final purification through repetitive reversed-phase HPLC. Structure elucidation was accomplished utilizing 1D and 2D NMR spectroscopic characterization of the natural products and comparisons with malyngamides A and B. DPFGSE 1D NOE data suggested a different geometrical stereochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Especially 3 J CH coupling constants follow the Karplus relation and build a more reliable tool for the determination of relative configurations as e.g. NOE connectivities, which often do not allow unambiguous conclusions [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Especially 3 J CH coupling constants follow the Karplus relation and build a more reliable tool for the determination of relative configurations as e.g. NOE connectivities, which often do not allow unambiguous conclusions [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The introduced DPFGSE-NOE method provides spectra without subtraction artifacts and thus allows the observation of NOE enhancements of as little as 0.02%. Milligan et al 17 used the DPFGSE-NOE spectra to determine the absolute configuration of olefins in some lipid extracts, which are secondary metabolites of the marine cyanobacterium Lyngbya majuscula; Liptaj et al 18 proved the DPFGSE-NOE experiment to be very useful for the observation of long-range NOE between the two xanthene units of biosynthesized neosatorin; Bauer et al 19 showed the advantage of DPFGSE-ROE in their study on calixarene derivatives, which are molecules of medium size. In this paper, we describe the elucidation of the conformation of compounds 1-4 using DPFGSE-NOE spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Spongistatin-1, 4 a famous natural product endowed with a nanomolar level of cytotoxicity, bears such a function too. Other examples include: welwistatin (3), 5 pinnaic acid (4), 6 malyngamide Q (5), 7 and penasin B (6), 8 but this list is not exhaustive. There are also pharmaceuticals that contain a vinyl chloride function, such as clomiphene (7), an anti-estrogen drug.…”
Section: Natural Products Containing a Vinyl Chloride Functionmentioning
confidence: 99%